Interactive governance of small-scale fisheries and aquaculture: Transdisciplinary challenges of community involvement - Msomphora, Mbachi Ruth (2018)
Successful fisheries governance requires stakeholder’s involvement from point zero. However, it is usually hard to achieve this, especially if the stakeholders have significantly different interests, knowledge and power. In this regard, authors in this field expect that a fisheries governance that entails sharing management responsibilities between the authorities and the resource users i.e. ‘co-management’ (Jentoft 1998) and more recently ‘results-based management’ (RBM) (Msomphora 2016) and that a transdisciplinary (Aguilar-Perera et. al) research approach will deliver better outcomes. The purpose of this paper is therefore to show how a theoretical framework can be established, on how, and to what extent, coastal communities, including those of small-scale fisheries people, can efficaciously be involved in the management of fisheries, including aquaculture. This question is explored using Northern Norway as a case study; with particular focus on how the increasing conflict between aquaculture and fjord-fisheries could be successfully reduced with the perspective of transdisciplinary and the interactive governance ERIN approach.